Oligomerization of a Cargo Receptor Directs Protein Sorting into COPII-coated Transport Vesicles - Sato, Ken (The American Society for Cell Biology, 2003)
Secretory proteins are transported from the endoplasmic reticulum (ER) to the Golgi complex in vesicles coated with coat protein complex II (COPII). The incorporation of certain transport molecules (cargo) into the COPII vesicles is thought to be mediated by cargo receptors. Here we show that Emp47p, a type-I membrane protein, is specifically required for the transport of an integral membrane protein, Emp46p, from the ER. Exit of Emp46p from the ER was saturable and dependent on the expression level of Emp47p. Emp46p binding to Emp47p occurs in the ER through the coiled-coil region in the luminal domains of both Emp47p and Emp46p, and dissociation occurs in the Golgi. Further, this coiled-coil region is also required for Emp47p to form an oligomeric complex of itself in the ER, which is essential for exit of Emp47p from the ER. Our results suggest that Emp47p is a receptor protein for Emp46p that allows for the selective transport of this protein, and this event involves receptor oligomerization.